Introducing NICE guidelines for intravenous fluid therapy into a district general hospital. Issue 1 (3rd February 2022) - McDougall, Marcia; Guthrie, Bruce; Doyle, Arthur; Timmins, Alan; Bateson, Meghan; Ridley, Emily; Drummond, Gordon; Vadiveloo, Thenmalar
Abstract : Background: National Institute for Health and Care Excellence (NICE) guidelines on intravenous fluid prescribing for adults in hospital, issued in 2013, advised less use of 0.9% sodium chloride than current practice, provided a logical system for prescribing and suggested further study of electrolyte abnormalities. Aims: To describe the steps taken to establish and monitor guideline introduction and to assess effects on clinical biochemistry results, in a general hospital setting. Methods: We used established principles of change to modify education, teaching, record keeping and audit throughout the hospital, changed the availability of intravenous fluid preparations in the wards and monitored the use of intravenous fluids. We anonymously linked local clinical chemistry records to nationally available patient records (NHS Scotland SMR01). We chose specified medical emergencies, and major emergency and elective general and orthopaedic surgery, where management would require intravenous fluids, for a two-phase cross-sectional study between 2007 and 2017, spanning the change in prescribing. Primary outcomes were abnormal bicarbonate, sodium, potassium and incidence of acute kidney injury (AKI), and secondary outcomes were mortality and length of stay. Results: Over the study period, sodium chloride 0.9% use decreased by 75%, and overall intravenous fluid use decreased from 0.65 to 0.40 L/occupied bed day. The incidence of acidosis decreased from 7.4% to 4.8% of all admissions (difference −2.7%, 95% CI −2.1 to −3.0). No important changes in other electrolytes were noted; in particular, plasma sodium values showed no adverse effects. Stage 1 AKI increased from 6.7% to 9.0% (difference 2.3%, 95% CI 1.6 to 3.0), but other causes for this cannot be excluded. Mortality and length of stay showed no adverse effects. Conclusions and implications: Effective implementation of the guidelines required substantial time, effort and resource. NICE suggestions of fluid types for maintenance appear appropriate, but prescribed volumes continue to require careful clinical judgement.